Food sovereignty and uncultivated biodiversity in South Asia essays on the poverty of food policy and the wealth of the social landscape - Majahara, Pharahada (Academic Foundation ; International Development Research Centre, 2007)
"This book is an eye-opener. It compels us to rethink what constitutes food security, women's knowledge systems, and common pool resources. It makes us see much that we would casually walk past, that we might never taste, that we cannot purchase. Flourishing in the interstices of the cultivated and the uncultivated, the public and the private, the field and the forest, are innumerable leafy greens, fruits, tubers, roots, small fish, grasses, and other forms of food life hidden from our gaze that constitute the daily diet of numerous villagers across South Asia. Based on a series of studies and practical experiments undertaken over several years by the Deccan Development Society in the drylands of Medak district in Andhra Pradesh (South India) and by UBINIG in the flood-plains of Tangail district in Bangladesh, this slim volume tells us some surprising facts about uncultivated foods. A dietary intake survey by the authors, of 50 families in 10 Bangladesh villages, for instance, found that uncultivated food provided, on average, 65% of the food weight and all of the fodder and fuel needs of very poor landless households, and 34% of the food weight and 20% of the fuel and fodder needs of better-off landed households. In other words, such plants are not just part of the coping strategy that the poor use during seasonal shortages or drought; they are part of the everyday sustenance and key sources of vitamins, minerals and proteins not just of the poor but also of the relatively well-off. In Medak district alone 79 species of uncultivated leafy greens used as food have been documented. Many plants also have medicinal properties. These uncultivated plants living as 'partner' plants alongside the cultivated ones inhabit a landscape unobserved by most researchers. They are neither 'wild' (unattended) nor 'domesticated' (tamed), but something in between community-managed. As the authors emphasize, this uncultivated biodiversity provides not just food security but food sovereignty. It gives people control over a basic need. Implicit in this volume, however, is also a much-needed warning. The biodiverse ecosystems and the local knowledge systems that sustain these food chains are threatened by the spread of 'modern' monocultural, chemically-driven agriculture and by large-scale displacements of people from their familiar environments. Among the undocumented and unmourned hidden costs of such 'development' initiatives is precisely the disappearance of knowledge about food systems based on the everyday use of local environments, especially by women. To keep these systems alive is not just the responsibility of the women and their families, nor just of the authors who have long provided these communities their dedicated support it is also the responsibility of all of us as a trust for the future."--excerpted from Foreword